Adaption des institutions Tradition-Nelles A La Gestion Foncierre De Kinshasa, Ville-Capitale (1960-2016) - Sangu, Philippe Ibaka (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.